The Challenging Landscape of Inventory Management - Gills, Brent; Thomas, Joseph Y.; McMurtrey, Mark E.; Chen, Alexander N. (American Journal of Management, 2020)
Inventory management is a critical practice that organizations occasionally review to ensure that it aligns with their overall objectives and strategies. The main processes of inventory management involve ordering, storing, and managing raw materials, finished products, and other vital components that require processing and warehousing. The size of the organization does not affect the need to have an advanced inventory management system, but it is worth identifying that some organizations have intricate supply chains due to the complexity of their manufacturing processes, and the need to balance the risk of improper inventory controls. This paper will go over some of the practices of inventory management and how companies utilize and benefit from them, as well as how new technology is shaping the field.